Effective ferromagnetic coupling between a superconductor and a ferromagnet in LaCaMnO/Nb hybrids - Stamopoulos, D.; Moutis, N.; Pissas, M.; Niarchos, D. (PHYSICAL REVIEW B, 2005)
In this work we present magnetization data on hybrids consisting of multilayers (MLs) of manganites [La0.33Ca0.67MnO3/La0.60Ca0.40MnO3](15) in contact with a low-T-c Nb superconductor (SC). Although a pure SC should behave diamagnetically in respect to the external magnetic field in our ML-SC hybrids we observed that the magnetization of the SC follows that of the ML. Our intriguing experimental results show that the SC below its T-c(SC) becomes ferromagnetically coupled to the ML. As a result in the regime where diamagnetic behavior of the SC was expected its bulk magnetization switches only whenever the coercive field of the ML is exceeded. By employing specific experiments where the ML was selectively biased or not we demonstrate that the ML inflicts its magnetic properties on the whole hybrid. Possible explanations are discussed in connection to recent theoretical proposals and experimental findings that were obtained in relative hybrids.